Strategic choices of the licensing system in the sector of construction and mining of mineral raw materials in Ukraine (Journal of Economic Research & Business Administration, 2015)
In the article discusses the alternative options for the development of economic policy in the sphere of subsoil use. On the basis of the Harberger’s model associated with the empirical measurement of the so-called „social costs of monopoly” revealed that the licensing regime in the subsurface could take into account the specificities of different sectors, even within a single sector of the national economy. Within the boundaries of the local industry, even its various sectors in varying degrees of intensity react to strengthen the processes of regulation and deregulation by the government. Economic sectors in which to start a business is not required large investments could easily circumvent administrative barriers and thus to suppress their growth is not enough direct unjustified restrictions and require special economic barriers. Economic sectors in which to start a business is not required large investments can easily circumvent administrative barriers and thus to suppress their growth is not enough direct unjustified restrictions and require special economic barriers. For the growth sectors that require large capital investments, it is necessary simply lowering the height of administrative barriers.
Keywords: economic policy; the use of mineral resources; licensed system; the economic effects; the social welfare; the specific sector of the national economy